Type I Photosensitization of 2′-deoxyadenosine 5′-monophosphate (5′-dAMP) by Biopterin and its Photoproduct Formylpterin - Serrano, Mariana Paula (2013)
Biopterin (Bip) and its photoproducts 6-formylpterin (Fop) and 6-carboxypterin (Cap) accumulate in the skin of patients suffering from vitiligo, a chronic depigmentation disorder where the protection against UV radiation fails because of the lack of melanin. These compounds absorb in the UV-A inducing a potential photosensitizing action that can cause damage to DNA and other biomolecules. In this work, we have investigated the capability of these pterin derivatives (Pt) to act as photosensitizers under UV-A irradiation for the degradation of 2′-deoxyadenosine 5′-monophosphate (5′-dAMP) in aqueous solutions, as model DNA target. Steady-state and time-resolved experiments were performed and the effect of pH was evaluated. The results showed that photosensitized degradation of 5′-dAMP was only observed under acidic conditions, and a mechanistic analysis revealed the participation of the triplet excited state of the pterin derivatives (3Pt*) by electron transfer yielding the corresponding pair of radical ions (Pt•− and 5′-dAMP•+), with successive photosensitizer recovery by electron transfer from Pt•− to O2. Finally, 5′-dAMP•+ participates in subsequent reactions to yield degradation products.